2019
DOI: 10.6004/jnccn.2018.7086
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Treatment Facility Volume, Therapy Types, and Overall Survival in Patients With Stage IIIA Non–Small Cell Lung Cancer

Abstract: Background: There is significant heterogeneity in the treatment of stage IIIA non–small cell lung cancer (NSCLC). This study evaluated the therapeutic and survival disparities in patients with stage IIIA NSCLC based on the facility volume using the National Cancer Database. Methods: Patients with stage IIIA NSCLC diagnosed from 2004 through 2015 were included. Facilities were classified by tertiles based on mean patients treated per year, with low-volume facilities treating ≤8 patients, intermediate-volume tre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 21 publications
1
7
0
Order By: Relevance
“…29,30 related to race and socioeconomic status. [28][29][30]33,34 Furthermore, we found that similar to other studies examining disparities in aspects of lung cancer care, there are significant differences in delivery of adjuvant therapy in relationship to geographic region, particularly in the west and south, which is likely related to access to care, density of providers, socioeconomic disparities, or rural versus urban settings. 7,14,33 Addressing disparities in cancer care is complex.…”
Section: Discussionsupporting
confidence: 83%
“…29,30 related to race and socioeconomic status. [28][29][30]33,34 Furthermore, we found that similar to other studies examining disparities in aspects of lung cancer care, there are significant differences in delivery of adjuvant therapy in relationship to geographic region, particularly in the west and south, which is likely related to access to care, density of providers, socioeconomic disparities, or rural versus urban settings. 7,14,33 Addressing disparities in cancer care is complex.…”
Section: Discussionsupporting
confidence: 83%
“…This is well illustrated by a recent paper including more than 83,000 patients presenting a stage III NSCLC treated in 1319 facilities. Those treated in a high volume centre (more than 15 patients) were more likely to have surgery or a trimodality and had significantly a lower risk of death [36]. This is one reason to look more to randomised trials to answer the question.…”
Section: Induction Chemoradiotherapy Before Surgerymentioning
confidence: 99%
“…While studies on the timeliness of access to treatment in OG cancers are scarce, one study found that a delayed surgical resection has no impact on long‐term survival 17 . However, treatment at larger treatment centres has been shown to culminate in better survival for both lung 18,19 and OG 20‐22 cancer patients. This evidence may suggest that the larger treatment centres have more streamlined care services than smaller centres, highlighting the benefits of service centralisation 4 .…”
Section: Introductionmentioning
confidence: 99%